Effect of electroacupuncture on discomfort during gastroscopy: A randomised controlled trial - Xuan Yin; Bingyu Yu; Philippa Jemma Hazlewood; Kun Xu; Hongyu Yue; Yiqun Mi; Shifen Xu (Elsevier, 2023)
Background: Gastrointestinal reactions, pain and discomfort are inevitable in patients undergoing common gastroscopy. Acupuncture is an effective therapy that assists in the perioperative period; however, evidence of it relieving discomfort is limited. We conducted this trial to observe the effect of electroacupuncture (EA) on discomfort caused by gastroscopy without sedatives. Methods: This was a single-centre, patient-assessor blind, randomised controlled trial. Sixty patients requiring gastroscopy were randomly assigned to the EA and control groups (sham acupuncture, SA, group) in a 1:1 ratio. Patients in the EA group underwent treatment at acupoints LI4 (Hegu), PC6 (Neiguan), ST36 (Zusanli), and ST34 (Liangqiu) for 30 min before gastroscopy, whereas patients in the SA group underwent superficial acupuncture at non-acupoints. The patients' nausea level, throat discomfort, bucking, and agitation were evaluated using a visual analogue scale (VAS) within 30 min after gastroscopy. The mean VAS score was the primary outcome. Secondary outcomes were the Amsterdam Preoperative Anxiety and Information Inventory Scale, used to evaluate patients' preoperative anxiety levels, and the 6-item State-Trait Anxiety Inventory (STAI-S6), used to assess anxiety before and after gastroscopy. The patients' vital signs, including heart rate, blood pressure, and pulse oxygen saturation, were recorded before, during, and after gastroscopy. Results: At 30 min after gastroscopy, the mean VAS score in the EA group (4.20 ± 0.63) was lower than that in the control group (5.14 ± 0.70, mean difference (MD): − 0.94, 95% confidence interval (CI): − 1.28, − 0.59, P < 0.001). There were statistically significant between-group differences in the nausea and vomiting, throat discomfort and agitation VAS scores (all P < 0.01), whereas no difference was found in the bucking VAS score (P = 0.692). Compared with the SA group, patients in the EA group had a 6.90-point lower in STAI-S6 (95% CI: −12.98, −0.81, P = 0.027) after gastroscopy. Patients in the EA group had a slower heart rate and lower blood pressure than those in the SA group. Serious adverse events were not observed during the trial. Conclusion: EA can help relieve patients' anxiety, and improve their nausea and vomiting, throat discomfort, and agitation during gastroscopy. Trial registration: Chinese Clinical Trial Registry (ChiCTR)ID: ChiCTR2000040726.